Sosialisasi Pemilahan Sampah Organik dan Anorganik Guna Meningkatkan Kepedulian Lingkungan Hidup di SD Kartika IX-I Jember - Adillia Natasya Saputri; Inge Wiliandani Setya Putri; Arik Aguk Wardoyo; Avisha Tita Sabbila; Ilfi Dwi Nurdiana (Edujavare Publishing, 2024)
The waste problem is one of several important problems experienced by Indonesia. However, community involvement in the urgency of waste management is still not optimal. Therefore, the aim of this research is to provide education about waste management as early as possible in order to minimize the negative impacts of waste. The target of this community service program is to increase elementary school students' awareness and knowledge about the importance of sorting waste and disposing of it properly according to its category. This community service program is carried out through socialization and direct experience, where students from SD Kartika IX-I Jember. Because the targets are at an early age, the method used is teaching how to sort organic and inorganic waste, how to recycle waste, and learning about the benefits of waste by socializing it and then giving a few games. It was concluded that ongoing support is needed from people in the environment around students, both teachers and parents, to encourage students to sort organic and inorganic waste in order to increase environmental awareness at SD Kartika IX-I Jember.